EFFECTIVITY OF PNEUMATIC RETINOPEXY PROCEDURE IN PRIMARY RHEGMATOGENOUS RETINAL DETACHMENT (RRD) - Soefiandi Soedarman; Soedarman Sjamsoe; Waldensius Girsang; Elvioza Elvioza; Referano Agustiawan; Gitalisa Andayani Adriono (Indonesian Vitreoretinal Society, 2020)
Introduction : To evaluate the effectiveness of pneumatic retinopexy (PR) for repair of primary rhegmatogenous retinal detachment (RRD) with respect to single operation success (SOS) and best corrected visual acuity (BCVA). Method : This retrospective review comprised 8 eyes with primary rhegmatogenous retinal detachment with superior break that undergone pneumatic retinopexy as the initial procedure between 2009-2014 at Jakarta Eye Center, Indonesia. Result : The mean age of subjects was 49 ± 14.35 years. Four subjects (50%) had Single operation had only done success after 6 months of observation. The eyes that failed single procedure underwent vitrectomy and silicon oil tamponade. Subjects that only done single procedure had better BCVA (0.01 ± 1,3 logMAR) compare to subjects that done secondary procedure (0.3 ± 0.42 logMAR) after 6 months of observation. Conclusion : Pneumatic retinopexy is still an effective procedure for primary rhegmatogenous retinal detachment with superior breaks although in our study the single operation success was 50%.